BIX-01294 increases pig cloning efficiency by improving epigenetic reprogramming of somatic cell nuclei. Issue 1 (January 2016) - Huang, Jiaojiao; Zhang, Hongyong; Yao, Jing; Qin, Guosong; Wang, Feng; Wang, Xianlong; Luo, Ailing; Zheng, Qiantao; Cao, Chunwei; Zhao, Jianguo
Abstract : Accumulating evidence suggests that faulty epigenetic reprogramming leads to the abnormal development of cloned embryos and results in the low success rates observed in all mammals produced through somatic cell nuclear transfer (SCNT). The aberrant methylation status of H3K9me and H3K9me2 has been reported in cloned mouse embryos. To explore the role of H3K9me2 and H3K9me in the porcine somatic cell nuclear reprogramming, BIX-01294, known as a specific inhibitor of G9A (histone-lysine methyltransferase of H3K9), was used to treat the nuclear-transferred (NT) oocytes for 14–16 h after activation. The results showed that the developmental competence of porcine SCNT embryos was significantly enhanced both in vitro (blastocyst rate 16.4% vs 23.2%, P <0.05) and in vivo (cloning rate 1.59% vs 2.96%) after 50 nm BIX-01294 treatment. BIX-01294 treatment significantly decreased the levels of H3K9me2 and H3K9me at the 2- and 4-cell stages, which are associated with embryo genetic activation, and increased the transcriptional expression of the pluripotency genes SOX2, NANOG and OCT4 in cloned blastocysts. Furthermore, the histone acetylation levels of H3K9, H4K8 and H4K12 in cloned embryos were decreased after BIX-01294 treatment. However, co-treatment of activated NT oocytes with BIX-01294 and Scriptaid rescued donor nuclear chromatin from decreased histone acetylation of H4K8 that resulted from exposure to BIX-01294 only and consequently improved the preimplantation development of SCNT embryos (blastocyst formation rates of 23.7% vs 21.5%). These results indicated that treatment with BIX-01294 enhanced the developmental competence of porcine SCNT embryos through improvements in epigenetic reprogramming and gene expression.